Evolu化 - Teo, Qi Yan (Nanyang Technological University, 2022)
Singaporean Chinese have created a unique identity that differs from Chinese from other parts of Asia mainly due to the cultural influences from other races in Singapore. With globalization, it exposes us to even more cultures and influences. Today, Singaporean Chinese have been speaking and using less Mandarin at home, school, and in social settings while interests in other aspects of their culture are deteriorating. How will Singaporean Chinese culture evolve to be in the future?